Effect of Nano and Organic fertilizers on some vegetative growth characteristics of Phoenix dactylifera C.V Khastawi - Thajil, Mahmoud M.; Blackt , Raad Taha Muhammad Ali (Journal of Kerbala for Agricultural Sciences, 2022)
The experiment was conducted in Al-Hussainiya palm plant / Holy Karbala governorate affiliated to the Ministry of Agriculture /Horticulture Department during the growing season of 2021 AD, with the aim of knowing the effect of nano-fertilizers and marine extracts on some vegetative growth characteristics of the date palm variety Al-Khastawi .A two-factor experiment was carried out according to a randomized complete block design (RCBD) with three replications, first factor was the addition of nano-fertilizer to the soil at four concentrations (0, 0.5,1 ,1.5 ml . liter-1. palm-1) while the second factor included spraying with algal extracts fertilizer at four concentrations (0, 1.5, 2.0 ,2.5 ml. liter-1. palm-1) where the nano-fertilizer was added to the soil by three additions and at the rate of one addition per month, while the spray treatment with algae fertilizer was six sprays between each spray and two weeks, and it was the first addition of nano-fertilizer to trees. The date palm was dated 1/3/2021, while the first application of algal fertilizer was on 3/3/2021. The results showed that the treatment with nano-fertilizer at a concentration of 1.5 ml. liter-1. palm-1 was significantly superior in most of the studied traits (leaf length 3.38 cm, wet weight 41.19 gm). Furthermore, the treatment of spraying with algal manure extract at a concentration of 2.5 ml. liter-1. palm-1 was significantly superior in most of the studied traits (leaf length 51.83 cm, dry weight 56.96%, chlorophyll 12.56 mg g-1). Additionally, the interaction between the two fertilizers, nano-fertilizer and marine algae extracts, showed significant superiority in all studied traits.